A new S-box construction method based on the fractional-order chaotic Chen system - Ozkaynak, Fatih; Celik, Vedat; Ozer, Ahmet Bedri (Springer London Ltd, 2017)
Since substitution box (S-box) is the only nonlinear component related to confusion properties for many block encryption algorithms, it is a necessity for the strong block encryption algorithms. S-box is a vital component in cryptography due to having the effect on the security of entire system. Therefore, alternative S-box construction techniques have been proposed in many researches. In this study, a new S-box construction method based on fractional-order (FO) chaotic Chen system is presented. In order to achieve that goal, numerical results of the FO chaotic Chen system for a = 35, b = 3, c = 28 and alpha = 0.9 are obtained by employing the predictor-corrector scheme. Besides, a simpler algorithm is suggested for the construction of S-box via time response of the FO chaotic Chen system. The performance of suggested S-box design is compared with other S-box designs developed by chaotic systems, and it is observed that this method provides a stronger S-box design.
Keywords: Chaos; Cryptology; S-box; FO Chen system; Predictor-corrector scheme